1998
DOI: 10.1021/cm980397u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cation Size on the Structural Features of Ln1/2A1/2MnO3 Perovskites at Room Temperature

Abstract: Sm, and Y 0.5 Sm 0.5) have been prepared, and structure determinations have been carried out at room temperature using high-resolution synchrotron X-ray powder diffraction data. The octahedral tilting distortion increases as the average ionic radius of the Ln/A cations, 〈r A 〉, decreases. The two crystallographically distinct Mn-O-Mn bonds [Mn-O(eq)-Mn and Mn-O(ax)-Mn] are almost identical for Ln 0.5 Ca 0.5 MnO 3 compounds, with the exception of La 0.5 Ca 0.5 MnO 3. The La 0.5 Ca 0.5 MnO 3 compound and the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
160
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(183 citation statements)
references
References 65 publications
22
160
0
1
Order By: Relevance
“…This uniaxial compression of the c-axis is in good agreement with a well established physical pic- ture. Indeed, the contraction of the c parameter is consistent with the stabilization of an A-type AFM phase and d x 2 −y 2 orbital ordering at high pressure 7,8,20,23 . In this framework, a simple way to quantitatively determine if further distortions are induced by pressure is to calculate the orthorhombic strain.…”
Section: Resultssupporting
confidence: 55%
“…This uniaxial compression of the c-axis is in good agreement with a well established physical pic- ture. Indeed, the contraction of the c parameter is consistent with the stabilization of an A-type AFM phase and d x 2 −y 2 orbital ordering at high pressure 7,8,20,23 . In this framework, a simple way to quantitatively determine if further distortions are induced by pressure is to calculate the orthorhombic strain.…”
Section: Resultssupporting
confidence: 55%
“…To illustrate the importance of this bond bending, we mention that it is comparable to that produced in R 0.5 Ca 0.5 MnO 3 perovskites series when going from R =Pr to the much smaller Sm ͑in this case, the change in V is −1.3%, at RT, and the change in the average Mn-O distance is 0.002 Å͒. 28 This comparison also allows to foresee that an important reduction in the space available for the cations at the A site of the perovskite must take place. This is confirmed by the abrupt reduction ͑on cooling͒ in the average A-O bond distance displayed in Fig.…”
Section: Discussionmentioning
confidence: 74%
“…increasing hr A i is equivalent to increasing the hydrostatic pressure, which increases the Mn-O-Mn bond angle and consequently the bandwidth. Detailed studies of the effect of hr A i on the electronic order have been reported by Woodward et al (1998). Systems with very large hr A i tend to be FM and metallic, with a Curie temperature T c that increases with hr A i.…”
Section: Electronic Orders In Rare-earth Manganitesmentioning
confidence: 99%